SISTEM PAKAR UNTUK MENDIAGNOSA HAMA DAN PENYAKIT TANAMAN PISANG BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstrak – Development of Information Technology push to take advantage of these developments included in the field of agriculture, including horticulture crops to have a high economic value, namely bananas.This study tries to build an expert system application, which can make identification of pests and diseases in banana plants, so it can provide a solution methods of controlling the disease. An analysis of a system is one of the processes that should be applied in the design of software. Because in this step is a step which outlines the parts of the system. In this system built application where the application is useful for diagnosing pests and diseases in banana plants. There are 41 symptoms that resulted in 10 diagnoses caused by pests and 10 diagnoses were caused by diseases of banana plants. This system uses forward chaining inference method that is tracking the fore. As the presentation of program the system uses Android base is more mobile and can be taken at the time of the detection of pests and diseases in the field and make it easier Keywords Banana, banana Pests, Diseases bananas, expert